COUNTING SYSTEM EMPLOYEES SALARY ON PT. PERKASA INDAH - Didin Hasanudin; Setijo Bidiutomo, Ir, MM Setijo Bidiutomo, Ir, MM (Jurnal Sistem Informasi, 2000)
At PT. PERKASA INDAH experiencing difficulties in calculating the payroll in thecompany. To the authors design a payroll calculation system that can help the processworks. With this system expected to improve the working efficiency for personnelbecause this system is very easy to operate. other than that the reports could becompleted in accordance with the time allowed. Until which produced more accurateinformation, quickly and precisely.